2017
DOI: 10.1016/j.wasman.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Critical management practices influencing on-site waste minimization in construction projects

Abstract: As a result of increasing recognition of effective site management as the strategic approach for achieving the required performance in construction projects, this study seeks to identify the key site management practices that are requisite for construction waste minimization. A mixed methods approach, involving field study and survey research were used as means of data collection. After confirmation of construct validity and reliability of scale, data analysis was carried out through a combination of Kruskal-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 53 publications
3
111
0
2
Order By: Relevance
“…However, most construction waste management studies have largely focussed on the actual construction stage, resulting into the strategies for achieving the 3Rsreduce, reuse and recycle (Osmani, 2012;Ajayi et al, 2017a). This is notwithstanding that waste management efforts at the construction stage is belated if the design and the whole design process is not waste-efficient, especially as up to 33% of building construction waste could be prevented through design activities (Innes, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, most construction waste management studies have largely focussed on the actual construction stage, resulting into the strategies for achieving the 3Rsreduce, reuse and recycle (Osmani, 2012;Ajayi et al, 2017a). This is notwithstanding that waste management efforts at the construction stage is belated if the design and the whole design process is not waste-efficient, especially as up to 33% of building construction waste could be prevented through design activities (Innes, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kong et al (2001) suggests that materials procurement could contribute up to 50% of project cost. Although, several studies have suggested ineffective coordination of materials procurement process as a key cause of construction waste (Formoso et al, 2002;Ajayi et al, 2017), procurement measures for waste mitigation have either remained unexplored or subjects of scattered and unfocussed findings.…”
Section: Introductionmentioning
confidence: 99%
“…Other measures cover agreements between contractors and subcontractors. These include a written commitment on waste management [15], contractual clauses to make subcontractors responsible for their waste [26], and the inclusion of waste targets for subcontractors [26,27].…”
Section: Fulfilling the Requirements Established By The Current Regulmentioning
confidence: 99%